Membrane Modulation of Super-Secreting “midiBacillus” Expressing the Major Staphylococcus aureus Antigen – A Mass-Spectrometry-Based Absolute Quantification Approach - Antelo-Varela, Minia; Aguilar Suárez, Rocío; Bartel, Jürgen; Bernal-Cabas, Margarita; Stobernack, Tim; Sura, Thomas; van Dijl, Jan Maarten; Maaß, Sandra; Becher, Dörte (Frontiers in Bioengineering and Biotechnology, 2020)
Bacillus subtilis has been extensively used as a microbial cell-factory for industrial enzymes due to its excellent capacities for protein secretion and large-scale fermentation. This bacterium is also an attractive host for biopharmaceutical production. However, the secretion potential of this organism is not fully utilized yet, mostly due to a limited understanding of critical rearrangements in the membrane proteome upon high-level protein secretion. Recently, it was shown that bottlenecks in heterologous protein secretion can be resolved by genome minimisation. Here, we present for the first time absolute membrane protein concentrations of a genome-reduced B. subtilis strain ('midiBacillus') expressing the immunodominant Staphylococcus aureus antigen A (IsaA). We quantitatively characterise the membrane proteome adaptation of midiBacillus during production stress on the level of molecules per cell for more than 400 membrane proteins, including determination of protein concentrations for ~61% of the predicted transporters. We demonstrate that ~30% of proteins with unknown functions display a significant increase in abundance, confirming the crucial role of membrane proteins in vital biological processes. In addition, our results show an increase of proteins dedicated to translational processes in response to IsaA induction. For the first time reported, we provide accumulation rates of a heterologous protein, demonstrating that midiBacillus secretes 2.41 molecules of IsaA per minute. Despite the successful secretion of this protein, it was found that there is still some IsaA accumulation occurring in the cytosol and membrane fraction, leading to a severe secretion stress response, and a clear adjustment of the cell’s array of transporters. This quantitative dataset offers unprecedented insights into bioproduction stress responses in a synthetic microbial cell.